Fear of catastrophic health expenditures and unrealistic expectations from supplementary health insurance: ethnic differences. Issue 4 (9th November 2018) - HaGani, Neta; Hayek, Samah; Tarabeia, Jalal; Yehia, Mohammad; Green, Manfred S
Abstract: Background: In Israel, the whole population is covered by comprehensive universal health insurance. Despite that, most of the population purchases supplementary health insurance (SHI). It has been shown that individuals purchase more health insurance and preventive medicine when they are uncertain of their state of health, while a majority may not fully understand basic concepts in their health insurance coverage. The purpose of this study was to examine the role of fear of catastrophic health expenditures and unrealistic expectations in purchasing SHI, which does not cover expenses for life-threatening illnesses. Methods: A cross-sectional survey was conducted among random samples of 814 Jews and 800 Arabs in Israel. A structured questionnaire was administered by telephone using random digit dialling. Log-linear regression was used to identify factors associated with reasons for purchasing SHI and expectations from SHI. Results: The most common reason for purchasing SHI was fear of catastrophic health-related expenditures (41%). The most important service expected from SHI was 'cancer medications' (mean 4.68 [standard deviation 0.87]). Differences in the reasons for purchasing SHI and in expectations from SHI were found according to population group, age, gender and education. Conclusions: Consumers' misconceptions and fear of catastrophic health expenditures are major factors leading to the purchase of SHI, despite universal health coverage. Improved and accessible information should help consumers make informed decisions as to whether or not to purchase SHI.